Law Enforcement Against Online Fraud Crimes: A Case Study at Police District Area of Wajo - Aswar Ardi; M. Said Karim; Haeranah Haeranah (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
The Internet has brought new realities to every human life, the internet has also changed distance and time to infinity. crimes that often occur in the internet media is fraud on behalf of online businesses in the name of internet media. the purpose of the study was to analyze the barriers in law enforcement against online crimes as well as the effectiveness of law enforcement against online fraud crimes in the wajo police jurisdiction. the type of research used in this study is empirical law research located in wajo police jurisdiction. The results showed that obstacles in law enforcement against online crimes In terms of Personnel or Investigator Aspects, Aspects of Facilities and Infrastructure, Budget Aspects, and Community Aspects while the effectiveness of law enforcement against online fraud crimes in the Wajo Police Jurisdiction is 1) substance that in the law enforcement system needs to take decisive action or see the legal basis of the criminal, and the basis of law enforcement to optimize and maximize its performance is the legal basis of Law No. 19 of 2016 on amendments to Law No. 11 of 2008 on information and electronic transactions Article 28 paragraph (1) and Article 378 in the Criminal Code, and Article 390 of the Criminal Code and law enforcement that is before the investigation, certain crimes have been known but the crime is not yet clear and it is not yet known who did it.